The Host's Speech Styles to Male and Female Guests on the 20 Under 20 Podcast - Stephanie Tedja; Esther Harijanti Kuntjara (Institute of Research and Community Outreach - Petra Christian University, 2023)
I conducted this study to investigate the speech styles used by Raymond Chin, the 20 Under 20 podcast host. I did this study to find the speech styles used by Raymond Chin when talking to his male and female guests. In addition, I observed the similarities and differences in the speech styles used by Raymond when talking to his male and female guests. In conducting this study, I used the theory of speech styles by Chaer and Agustina (2014). Furthermore, this study was done using the qualitative approach. I found From this study that Raymond used the consultative, casual, and intimate speech style toward his male and female guests. Raymond also employed an additional formal speech style toward his female guest. This study shows that Raymond experiences speech accommodation which causes Raymond to, consciously or unconsciously, adapt his speech style based on the gender of his guest.